Pengaruh Orientasi Politik Terhadap Partisipasi Perempuan Muda Pada Pilpres 2024 : (Studi Empiris Terhadap Pilihan Politik Mahasiswi Ppkn Stambuk 2023) - Martua Felix Jonatan Simanullang; Nike Margaretha BR Sembiring; Griyani Elisabeth Purba; Bella Ayu Anzalia; Rani Oktavia Purba; Pingky Monica Hasugian; Halimah Halimah; Prayetno Prayetno (Doktrin: Jurnal Dunia Ilmu Hukum dan Politik, 2024)
Young women's political participation is the main focus in the context of inclusive and representative democracy. However, there are significant challenges in encouraging their participation in the political process, especially in general elections such as the 2024 Presidential Election. Although young women have great potential to influence the outcome of general elections, factors such as their political orientation can influence their level of participation. This research uses qualitative methods with a case study approach to understand the influence of political orientation on the political participation of young women, especially PPKn Stambuk 2023 students. The focus of this research is to explore the perspectives, experiences and views of female students regarding their participation in the 2024 presidential election. Political orientation refers to views , attitudes, and individual values ​​towards politics, which can greatly influence young women's political participation. In the context of the 2024 presidential election, young women's political orientation can influence how they decide to get involved in the political process, such as voting, campaigning or political discussions. Young women with a strong and informed political orientation tend to be more active in participating because they feel that their participation can make a difference. In contrast, young women with a weak or apathetic political orientation may be less involved due to a lack of belief that their participation will have an impact.